Association between major depressive disorder or depressive symptoms and the risk of vascular complications among patients with type 2 diabetes, and the mediating role of metabolic biomarkers: an analysis of the UK Biobank cohortResearch in context - Guochen Li; Yongfu Yu; Chunqing Lin; Shichen Zheng; Hong Tu; Wanghong Xu (EClinicalMedicine)
Summary: Background: Depression is a severe mental disorder commonly co-morbid with diabetes, but it remains to elucidate whether depression is associated with the risks of a wide range of vascular complications in people with type 2 diabetes mellitus (T2DM) and whether metabolic biomarkers may mediate this pathway. Methods: We conducted this prospective analysis among the participants of the UK Biobank who were diagnosed with T2DM and free of vascular complications at baseline between March 13, 2006 and September 30, 2010. Major depressive disorder (MDD) was ascertained according to the hospital admission records and self-report of doctor-diagnosed conditions, while the presence of depressive symptoms was assessed using the Patient Health Questionnaire-2. Cox proportional hazards models were performed to estimate the hazard ratios (HRs) and 95% confidence intervals (CIs) of MDD and depressive symptoms with the risks of incident heart failure (HF); total and individual atherosclerotic cardiovascular disease (ASCVD) including coronary artery disease (CAD), ischemic stroke (IS), and peripheral artery disease (PAD); total and individual microvascular complications of diabetic kidney disease (DKD), diabetic retinopathy (DR), and diabetic neuropathy (DN). Mediation analyses were conducted to quantify the potential mediation effects of circulating metabolites (involved in insulin-resistance, lipid profile, liver function, renal function, and inflammation) in the association of MDD with the outcomes. Findings: Of the total 23,856 patients with T2DM in the UK Biobank, 13,706 participants (61% males) were eligible and included in this study. During an average of 13 years of follow-up, 2927 (21.36%) ASCVD, 1070 (7.81%) HF, and 2579 (18.82%) microvascular complications occurred. The adjusted HR (95% CI) for MDD was 1.32 (1.09–1.61) with HF, 1.17 (1.03–1.32) with ASCVD, and 1.29 (1.14–1.46) with microvascular complications, while those for depressive symptoms were 1.47 (1.20–1.79), 1.25 (1.10–1.42) and 1.20 (1.05–1.37), respectively. The HRs ranged from 1.26 (1.09–1.44) to 1.96 (1.57–2.45) for MDD with individual complications and mortality, and from 1.26 (1.08–1.47) to 1.49 (1.16–1.93) for depressive symptoms. Up to 7.8% of adverse complications were attributable to MDD and 3.8% to depressive symptoms. A series of circulating metabolites involving lipid profile, renal function, and inflammation were observed to mediate the associations of MDD with vascular complications. The identified mediators jointly accounted for 7.29%–26.87% of the disparities in incident vascular complications between patients with and without MDD. Interpretation: Our findings highlight the role of MDD and depressive symptoms in the development of vascular complications among people with T2DM, and suggest that the effect of improving mental health on vascular outcomes in patients with T2DM should be investigated in future work. Funding: Three-Year Public Health Action Plan of Shanghai.